ショウワキチ ジョウクウ ニオケル タイリュウケン オゾン ノウド ト タイキ ノ ユソウ - 村山, 昌平; ムラヤマ, ショウヘイ; 青木, 周司; アオキ, シュウジ; 中澤, 高清; ナカザワ, タカキヨ; Murayama, Shohei; Aoki, Shuhji; Nakazawa, Takakiyo (1997)
P(論文) 1989年5月から1990年1月にかけての極夜を除く期間に南極昭和基地において対流圏O_3濃度の航空機観測が行われた。観測期間中, 上空ほどO_3濃度は高かった。対流圏下部のO_3濃度の変化は地上O_3濃度とよく似ており, 冬に最高値, 夏に最低値が現われる顕著な季節変化を示した。一方, 対流圏上部では冬に高濃度が現われた後, 9月-11月上旬にかけて徐々に減少し, その後再び増加した。結果として, 鉛直方向の濃度差は晩秋～早春に縮小し, 他の季節には増大した。これらの結果から, 高度によって異なる大気輸送過程の季節変化が昭和基地上空における対流圏O_3濃度の季節変化に影響を及ぼしていることが示唆された。 Aircraft measurements of the tropospheric O_3 concentration were made over Syowa Station, Antarctica from May 1989 to January 1990,except during the polar night months of June and July. The O_3 concentration increased with height for the whole period of the measurements. Lower tropospheric O_3 concentration showed a prominent seasonal variation with maximum concentration in winter and minimum in summer, which is very close to the result of continuous O_3 measurements at Syowa Station. In the upper troposphere, the concentration reached high values in winter, decreased gradually from September to early November and then increased again. As a result, the height-dependent difference of the concentration was reduced from late fall to early spring and enhanced in the remaining seasons of the year. From these results, it is hypothesized that the seasonal variation of height-dependent atmospheric transport processes could influence that of the tropospheric O_3 concentration over Syowa Station. departmental bulletin paper